Change Management And Employee Engagement Impact To Transformational Lead-ership And Organizational Restructuring Processes At PT. XZ - Dwitya Tanti Wigraha; Anandha Budiantoro (Eduvest - Journal of Universal Studies, 2024)
As an Agent of Development and an extension of the hands of the government, BUMN provides significant influence both for the development of the national economy, as well as providing services in meeting the needs of the community. The establishment of the BUMN Holding is a strategic government effort to regulate the management of the company following its affiliation. On April 11, 2018, the government through the Ministry of BUMN formed the Oil and Gas Holding (Migas), and PT XZ became one of its subholdings. This study aims to identify and study the impact of change management and employee attachment on transformational leadership and the process of organizational restructuring at PT XZ, during the holding process. The research method is quantitative through a questionnaire conducted against the employees of PT XZ of 220 respondents, with the method of data analysis using the program Analysis of Moment Structure (AMOS) 26.0. The results of the research show that: 1) change management has a significant influence on transformational leadership, 2) employee engagement has a meaningful influence upon transformational leadership, 3) change management have a significant impact on the process of organizational restructuring, 4) employee engagement has a significant influence over the organization's restructural process, and 5) transformation leadership has a signifying impact on organization restructuration process.